Penguatan Jati Diri Bangsa Melalui Moderasi Beragama sebagai Wujud Keberagaman yang Harmonis di Desa Widodaren, Kecamatan Gerih, Kabupaten Ngawi - Iman Pasu Marganda Hadiarto Purba; Bambang Sigit Widodo; Siti Makrufah; Silkania Swarizona (Indonesia Bergerak : Jurnal Hasil Kegiatan Pengabdian Masyarakat, 2025)
Indonesia, as a pluralistic nation, faces significant challenges in maintaining social harmony amidst increasing globalization and cultural disruption. One strategy to strengthen the nation's ideological resilience is through religious moderation based on the values ​​of Pancasila and multiculturalism. This Community Service (PKM) activity was carried out in Widodaren Village, Gerih District, Ngawi Regency, with the aim of fostering tolerance, strengthening national identity, and internalizing the values ​​of religious moderation in community life. The implementation method includes three stages: preparation, implementation, and evaluation. The implementation stage includes Training for Anti-Radicalism and Intolerance Cadre Facilitators (KANIRA), a Religious Moderation Workshop, interfaith mutual cooperation activities, and a Village Diversity Festival. A participatory approach was implemented so that the community is actively involved in the entire activity process. All activities were carried out with a participatory approach so that the community can understand and internalize the values ​​of moderation contextually. The program's implementation has demonstrated the growth of dialogue, interfaith cooperation, and a spirit of togetherness among residents in daily life. The positive response from the community and village officials demonstrates that a value-based approach to religious moderation can be an effective means of strengthening national identity at the local level.